Komparace vybraných lékařských knihoven z hlediska služeb - Hlůšková, Linda (2007)
Diploma thesis “Comparison of selected medical libraries in aspect of services“ concentrates to medical libraries. Essential notions, connected with medical libraries are introduced in introduction and there is determinated their actual situation. Important questions about medical libraries, legislative linked with their functioning, education of employees, institution, project VISZ are detected here. This thesis is based on comparison of 3 medical libraries which are primarily different (location of library, heterogeneity of users etc.). Area of comparison is rendition of services of medical libraries, their quality, availability, propagation etc. That’s why at the first every single library is described individually, its elementar data, such as location, availability, categories of users, content a character of documents. In the next part particular types of services are described. The most important issue is comparison of three selected medical libraries. They are analyzed